Effect of Surface Treated Silicon Dioxide Nanoparticles on Some Mechanical Properties of Maxillofacial Silicone Elastomer - Sara M. Zayed; Ahmad M. Alshimy; Amal E. Fahmy (International Journal of Biomaterials)
Current materials used for maxillofacial prostheses are far from ideal and there is a need for novel improved materials which mimic as close as possible the natural behavior of facial soft tissues. This study aimed to evaluate the effect of adding different concentrations of surface treated silicon dioxide nanoparticles (SiO2) on clinically important mechanical properties of a maxillofacial silicone elastomer. 147 specimens of the silicone elastomer were prepared and divided into seven groups (n=21). One control group was prepared without nanoparticles and six study groups with different concentrations of nanoparticles, from 0.5% to 3% by weight. Specimens were tested for tear strength (ASTM D624), tensile strength (ASTM D412), percent elongation, and shore A hardness. SEM was used to assess the dispersion of nano-SiO2 within the elastomer matrix. Data were analyzed by one-way ANOVA and Scheffe test (α=0.05). Results revealed significant improvement in all mechanical properties tested, as the concentration of the nanoparticles increased. This was supported by the results of the SEM. Hence, it can be concluded that the incorporation of surface treated SiO2 nanoparticles at concentration of 3% enhanced the overall mechanical properties of A-2186 silicone elastomer.